O diabo entrou na igreja: carnalização do sagrado em “Charivari”, de Lourdes Ramalho - Arruda, Maria do Socorro Araújo de (2009)
This work consist on the study of the meaning of charivari at Lourdes Ramalho’s (1997), homonymous book. The gool of the research is to demonstrate the carnavalization of moral volues and the ethic principles established by medieval Doutrine Cotholic Church and reveal the main transformations introduced by the literry work of the mentioned authoress. Based on the theoretical ideas on culture and popular literature written by Burke (1989), on the perpective of the carnivalization created by Bakhtin (1999), and on the menipéia satire constituted by Vasconcelos (1996), besides on the theoretical studyies about medieval cahrivari researched by Minois (2003), Berthold (2001) and Trompson (1998), on the sex nations as a deviation and Devil’s creation instituted by Barros ( 2001), Richards (1993) and sucuteri (1985), and finally on the symbolic and imaginary conception studied by Durand(2002), this work showed the unholy process and the valorization of exacerbate Eros suitable with the characters actions emphasing the simbolic, alegoric and methaphoric meanings of the Devil’s acts as the responsible transformer of this process. The comparative method was used at this work, showing that, through the analysis of the characters actions, both: the Lourdes Ramalho ideas and the similarity with the differences between these ideas and the medieval charivari in order to conclude that even tough there are structural, formal and contentness resemblances, it should be understandable that the main difference is reported to charivari’s function at Lourdes Ramalho book, because, in his opposition, the medieval charivari had the objectives to eliminate defects, bad habits and human limitations related to the conjugal infidelity and the sexual behaviours condemned by the church, and the Ramalho’s charivari discharges and exalts the absolute etotic pleasure.